2008
DOI: 10.1002/jmri.21429
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of hepatocellular carcinoma and colorectal liver metastasis by means of perfusion MRI

Abstract: Purpose: To characterize and compare hepatocellular carcinoma and liver metastases of colorectal metastatic cancer (CMC) by means of quantitative liver perfusion MRI. Materials and Methods:Liver perfusion was assessed in 26 HCC and CMC patients (50 nodules) by means of contrast-enhanced MRI. Six perfusion parameters-hepatic perfusion index (HPI), mean transit time (MTT), distribution volume (DV), total blood flow (F T ), arterial blood flow (F A ), and portal blood flow (F P )-were calculated in tumor nodules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
60
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 34 publications
11
60
1
Order By: Relevance
“…In contrast, CT perfusion imaging has not been evaluated for earlier detection of HCC in a surveillance program. This is likely due to the high higher in HCC than in hypovascular metastases (64).…”
Section: Ct Perfusion Parametersmentioning
confidence: 98%
“…In contrast, CT perfusion imaging has not been evaluated for earlier detection of HCC in a surveillance program. This is likely due to the high higher in HCC than in hypovascular metastases (64).…”
Section: Ct Perfusion Parametersmentioning
confidence: 98%
“…Tracer kinetic modeling based on DCE-MRI has been used to detect liver fibrosis and cirrhosis and to assess tumor angiogenesis [1217]. Recent studies using perfusion CT [1820] and DCE-MRI [16, 2124] showed potential for quantifying perfusion of malignant liver lesions and for monitoring treatment response to antiangiogenic drugs in liver metastases. However, perfusion CT [1820, 25] and DCE-MRI [16, 22, 2628] data assessing HCC lesions and cirrhosis are limited.…”
mentioning
confidence: 99%
“…Recent studies using perfusion CT [1820] and DCE-MRI [16, 2124] showed potential for quantifying perfusion of malignant liver lesions and for monitoring treatment response to antiangiogenic drugs in liver metastases. However, perfusion CT [1820, 25] and DCE-MRI [16, 22, 2628] data assessing HCC lesions and cirrhosis are limited. Some studies have shown differences in perfusion parameters between HCC tumors and background liver using perfusion CT [1820] or a 2D gradient-recalled echo sequence for DCE-MRI [16].…”
mentioning
confidence: 99%
“…Mechanical stress from increased intratumoral pressure, resulting in vessel compression may in part explain the observed difference (36). Furthermore, lower perfusion values in McA tumors may indicate a vascular supply similar to that of liver metastases rather than HCC (12). Also growth kinetics in McA tumors on average, are higher compared with DEN tumors possibly related to a less mature vascular phenotype in McA tumors.…”
Section: Tumor Heterogeneitymentioning
confidence: 96%
“…The marker enzymes of liver damage, aspartate aminotransferase (ASAT) alanine aminotransferase (12), cholinesterase (ChE), and gamma-glutamyl transpeptidase (GGT) were analyzed in serum samples of all rats (Diasys) following the manufacturer's instructions.…”
Section: Serum Biochemistrymentioning
confidence: 99%